2009
DOI: 10.1258/rsmsmj.54.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Local Corticosteroid Injection and Anti-inflammatory Medication in Carpal Tunnel Syndrome

Abstract: The results showed that neither of the groups demonstrated superior results. We conclude that local steroid injection and NSAIDs with concomitant use of wrist splints may offer patients with CTS variable and effective treatment options for the management of functional scores and nerve conduction parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
2
9
0
3
Order By: Relevance
“…Other modalities such as local corticosteroid injection (Deniz et al 2012) and surgical decompression (Evcik et al 2007) can significantly improve SNCV and the sensory nerve action potential amplitude of the median nerve. However, others have reported no improvement (Gurcay et al 2009). Deniz et al suggested that single injection of dexamethasone sodium phosphate significantly improves sensory and motor nerve conduction values when compared to baseline values (Deniz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other modalities such as local corticosteroid injection (Deniz et al 2012) and surgical decompression (Evcik et al 2007) can significantly improve SNCV and the sensory nerve action potential amplitude of the median nerve. However, others have reported no improvement (Gurcay et al 2009). Deniz et al suggested that single injection of dexamethasone sodium phosphate significantly improves sensory and motor nerve conduction values when compared to baseline values (Deniz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The functional states scores improved in both groups at month 3 compared with baseline, with no difference between the groups. At month 3, there were no significant differences for electrophysiologic parameters between groups [43]. …”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…Physicians often prescribed nonsteroidal anti-inflammatory drugs (NSAIDs), which our panelists recommended against based on randomizedcontrolled-trial data showing no benefit for CTS symptoms. 23,[33][34][35][36] (Other recent sources suggest that a trial of NSAIDs may be appropriate for some patients. 37 )…”
Section: Resultsmentioning
confidence: 99%